PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN (SMK) PROGRAM KEAHLIAN TEKNIK KOMPUTER DAN INFORMATIKA - Santoso, Edy (PT. Solusi Komunikasi Terapan, 2023)
This research is because of the low motivation of the students in learning. This research aims to know how big of the influences of the the teachers competence among their pedagogical, personality, sociality and professionality for students motivation in learning both partially or simultaneously. The method for this research is the survey method with quantitative approach. The population used is the eleventh grade students from computer and information engineering program of Pasundan 2 Vocational School Cimahi and PGRI 3 Vocational School Cimahi. The amount are 54 students. All of them are as the sample of the research. The result shows that patially, (1) The teacher pedagogical competence has the positive influence for the student’s motivation in learning, it gets 30,46%. (2) The teacher personality competence has the positive influence for the student’s motivation in learning, it gets 9,84%, (3) The teacher social competence has the positive influence for the student’s motivation in learning, it gets 18,06%, (4) The teacher professional has the positive influence for the student’s motivation in learning, it gets 13,43%, and simultaneously (5) Pedagogical, personality, social and professional for the teacher competence has the positive effect to motivate students in learning, it is 71,79% and 28,21% is determined by the other variables. Based on the results of the research it can be concluded that the pedagogical, personality, sociality and professionality competence of teachers partially and simultaneously has a positive influence for the student’s motivation in learning.